ChemInform Abstract: Recent Developments in Biological Water Oxidation. Issue 46 (October 2016) - Perez‐Navarro, Montserrat; Neese, Frank; Lubitz, Wolfgang; Pantazis, Dimitrios A.; Cox, Nicholas
Abstract: Review: 49 refs.